Late Quaternary Vegetation Development Following Deglaciation of Northwestern Alexander Archipelago, Alaska - Ager, Thomas A. (Frontiers in Earth Science, 2019)
The Cordilleran Ice sheet covered most of southeastern Alaska during the Last Glacial Interval (LGI: Marine Isotope Stage 2). Ice began to recede from western Alexander Archipelago ~17,000 + 700 yr BP. In this study, pollen analysis and radiocarbon dating of three sediment cores were used to reconstruct, for the first time, the postglacial development of vegetation of the northwestern Alexander Archipelago during the past ~15,240 cal yr. Hummingbird Lake (HL), on southwestern Baranof Island, yielded a sediment core with one of the longest dated records from southeastern Alaska. The earliest part of the HL pollen record (~15,240-14,040 yr BP) indicates that the earliest vegetation was pine (Pinus contorta subsp. contorta) parkland with willows (Salix), heaths (Ericaceae), sedges (Cyperaceae), grasses (Poaceae), herbs and ferns. Starting at ~14,040 yr BP, alder (Alnus) rapidly colonized the area as pine populations declined. By 11,400 yr BP, Sitka spruce (Picea sitchensis) colonized the area, and soon became the dominant conifer. Mountain hemlock (Tsuga mertensiana) also colonized the area by ~11,400 yr BP, followed by western hemlock (Tsuga heterophylla) at ~10,200 yr BP. By ~9200 yr BP, western hemlock had become the dominant species in the area. During the late Holocene yellow cedar (Chamaecyparis nootkatensis) became established. Two marine sediment cores were also analyzed for pollen, with the oldest core from Lower Sitka Sound, between Kruzof and Baranof Islands. The lower part of the core consists of interlayered tephras and freshwater lake muds that are estimated to be ~14,000 yr BP to 13,150 yr BP. Pollen evidence indicates that the early postglacial vegetation around Sitka Sound was pine parkland with alders and abundant ferns. Damage to vegetation around Sitka Sound by volcanic eruptions is suggested by abrupt, large shifts in percentages of alder and pine pollen, and fern spores in samples adjacent to tephra layers. A marine sediment core from Slocum Arm, a fiord on the western coast of Chichagof Island, has a basal age of ~10,000 yr BP. The pollen record is similar to the Holocene pollen record at Hummingbird Lake.